ANARKIS EPISTEMOLOGIS PAUL KARL FEYERABEND DAN RELAVANSINYA DALAM ILMU KEAGAMAAN - Nyak Mustakim (AZKIA : Jurnal Aktualisasi Pendidikan Islam, 2019)
This paper describes the thoughts of Paul F.K. Feyerabend. Feyerabend is a figure known as "anarchist". Feyerabend's philosophical thoughts will later be used to make a contribution to the epistemology of interpretation. The discussion that becomes the focal point of this paper is exploring Feyerabend's "anarchist" thinking, then looking for its relevance to religious science, namely the interpretation of the Qur'an, especially with regard to standardization of truth or benchmarks of truth in interpretation. While the results of the research in this paper are Feyerabend's philosophical thoughts can be used as a basis for critical, correct, tough, firm thinking, so that commentators of interpretation can position the interpretation in a firm position of truth, not mixed up with other truths. Philosophical thinking like this will be proven, later, used to provide a direction of thought that can fill the shortcomings in the tradition of Islamic education thought, in this case is the science of interpretation. This paper deliberately does not provide technical examples of the correctness of an interpretation, but aims to provide a broad sketch of thoughts on the interpretation of interpretation, from an epistemological perspective, especially in the field of interpretive methods.